Design and Motion Control of a Novel Weak-coupling Parallel Hip-joint Rehabilitation Mechanism - Xing Jiyuan; Xu Jilong; Liu Fucai (Jixie chuandong)
Aiming at the people with hip joint dysfunction, a novel weak-coupling parallel hip-joint rehabilitation mechanism is proposed. The mechanism and human lower limbs form a closed motion chain, so that it has three rotational degrees of freedom, and its rotation center coincides with the human hip joint center, which can meet the need of hip-joint rehabilitation. The human-machine inverse kinematics model is established using the closed loop vector method. The human-machine forward kinematics model is established using the numerical method. The fuzzy adaptive proportional-derivative (PD) controller is designed based on the fuzzy control theory. The control law is constructed using the tracking error and its derivative. The parameters of controllers are adaptively adjusted online using the fuzzy algorithm. The simulation and experiment results show that the fuzzy adaptive PD controller has fast response speed and good tracking effect.